Use of cefovecin in dogs and cats attending first‐opinion veterinary practices in Australia. (21st August 2020) - Hardefeldt, Laura; Hur, Brian; Verspoor, Karin; Baldwin, Timothy; Bailey, Kirsten E; Scarborough, Ri; Richards, Suzanna; Billman‐Jacobe, Helen; Browning, Glenn Francis; Gilkerson, James
Abstract : Background: Cefovecin is a long‐acting third‐generation cephalosporin commonly used in veterinary medicine. Third‐generation cephalosporins are critically important antimicrobials that should only be used after culture and susceptibility testing. The authors describe the common indications for cefovecin use in dogs and cats, and the frequency of culture and susceptibility testing. Materials and methods: A cross‐sectional study was performed using clinical records extracted from VetCompass Australia. A previously described method was used to identify records containing cefovecin. The reason for cefovecin use was annotated in situ in each consultation text. Results: Over a six‐month period (February and September 2018), 5180 (0.4 per cent) consultations involved cefovecin administration, of which 151 were excluded. Cats were administered cefovecin more frequently than dogs (1.9 per cent of cat consultations and 0.1 per cent of dog consultations). The most common reasons for cefovecin administration to cats were cat fight injuries and abscesses (28 per cent) and dermatitis (13 per cent). For dogs, the most common reasons for cefovecin administration were surgical prophylaxis (24 per cent) and dermatitis (19 per cent). Culture and susceptibility testing were reported in 16 cases (0.3 per cent). Conclusion: Cefovecin is used in many scenarios in dogs and cats where antimicrobials may be either not indicated or where an antimicrobial of lower importance to human health is recommended.